Kardioversi Listrik yang Berhasil pada Wanita Kehamilan Tahap Akhir dengan Takikardia Supraventrikular - Setiaji, Dimas; Jati, Lintang Daru; Shiddiq, Achmad; Hartopo, Anggoro Budi; Arso, Irsad Andi (Jurnal Kardiologi Indonesia, 2023)
Background: Pregnancy, precipitate cardiac arrhythmia, and supraventricular tachycardia (SVT) are some most frequent and sustained arrhythmias in pregnancy. In general, the pharmacological approach in pregnant patient is similar to that in the non-pregnant patient. However, fetal safety becomes a special consideration before administering the therapy. Case Presentation: We reported a 34-year-old female G3P2A0 with 35 weeks of gestation who came to the emergency department with sudden onset palpitations within 2 hours before admission. She had no prior history of any major medical illness. The clinical examination revealed that the patient had a regular pulse rate of 198/minute, and the blood pressure was 80/50 mmHg. The electrocardiogram showed the presence of SVT. Synchronized cardioversion with 50 joules was performed. The patient’s rhythm was converted to sinus tachycardia with a pulse rate of 120/minute and blood pressure was 90/60 mmHg. The patient was admitted to ICCU immediately after cardioversion and discharged from the hospital without any adverse effects after two days of monitoring. Conclusion: SVT is arrhythmia condition that is often found in pregnant women. In an unstable SVT condition, cardioversion is the first general action that is safe to be performed on the mother and the fetus. It must have strict observation before and after cardioversion to monitor whether there was a problem with the fetus or not.